NEEDS ANALYSIS AS THE FIRST STEP OF ARTICULATE STORYLINE ASSISTED LEARNING MEDIA DEVELOPMENT - Ayu Harlinda; Suratmi (Jurnal Cakrawala Pendas, 2024)
This study aims to analyze students' needs for learning media assisted by Articulate Storyline as a way to improve students' critical thinking skills. The research method used was development research with the ADDIE development model, but this research only reached the analysis stage. Data collection involved literature study and field study. The literature study was conducted by collecting relevant research and sources and analyzing the curriculum used by the school, while the field study was conducted by interviewing teachers and students of grade VI SD Negeri 74 Palembang, observation, critical thinking skills test, and documentation. Data analysis was conducted using the concept of Miles and Huberman which includes data reduction, data presentation, and conclusion. The results showed that students had varied characteristics and critical thinking skills. The average percentage of overall critical thinking ability is 37% with a low category. IPAS Phase C Learning Outcomes on Earth rotation material require students to be able to think critically. Students show enthusiasm when using learning media involving technology. Teachers and students agreed that they need Articulate Storyline learning media, which has several features to train critical thinking skills. The app allows the integration of different types of media such as video, audio, image, text and animation in one platform, which can enrich learning materials and trigger deep thinking. Based on the findings, it can be concluded that there is a need to develop learning media assisted by Articulate Storyline to improve students' critical thinking skills.